Peningkatan Ekonomi Petani Kopi Melalui Diseminasi Teknologi Mesin Pengupas Berbasis Motor Desa Lobang, Batang - umiyati, rini - (Journal of Dedicators Community, 2022)
Lobang Village, Limpung District, Batang Regency is one of the coffee-producing centers in Batang City. Quite remote area and low quality of human resources were the challenge for regional progress. This causes the need for modern technology to become one of the problems faced by coffee farmer groups in Lobang village which causes low productivity and quality of coffee produced. The technology dissemination service activity of UPGRIS service team aims to improve economy and welfare of residents, especially coffee farmers. The methods used include; observation, interviews, collecting data on the conditions and problems that faced by partners, then conducting discussions and socializing solutions that can be resolved to partners, followed by the implementation of activities as well as mentoring and evaluation. Technology dissemination service activities are carried out through increasing coffee production capacity with the introduction of motor-based fresh red coffee skin peeling machine technology, the introduction of the somatic embryogenesis method as a regeneration method that is able to produce superior and quality coffee plant and fruit seeds. Making various coffee-based products to help improve the family's economy, as well as delivering materials on sales, marketing and financial management that will assist residents in managing their businesses.